Cognitive Assessment Tools for Screening Older Adults With Low Levels of Education: A Critical Review - Tavares-Júnior, José Wagner Leonel; de Souza, Ana Célia Caetano; Alves, Gilberto Sousa; Bonfadini, Janine de Carvalho; Siqueira-Neto, José Ibiapina; Braga-Neto, Pedro (Frontiers in Psychiatry, 2019)
Introduction: Cognitive assessment of illiterate or low-educated people is particularly challenging because several battery tasks require a certain educational background. Early detection of mild cognitive impairment (MCI) using validated screening tools in older adults is of great importance since they are the target population group that could benefit from new drugs that are being investigated in clinical trials for the treatment of dementias. The assessment of psychometric properties of cognitive tests are not well established in patients with low education. The present study aimed to critically review the literature on cognitive assessment tools used for screening cognitive syndromes including MCI and AD in older adults with low education. Methods: We searched cross-sectional and prospective studies with adults over 55 years of age through a systematic electronic search of the following databases: MEDLINE, LILACS, Cochrane, and SCOPUS. Results: A significant number of assessment tools available (total of 44), but only a few of them showed diagnostic accuracy for the diagnosis of MCI and AD in adults with low education: Mini-Mental State Exam, Montreal Cognitive Assessment, Persian test of Elderly for Assessment of Cognition and Executive function and The Six Item Screener and Memory Alteration Test. Few studies evaluated adults with low education with range of cutoff scores for various cognitive test batteries. Conclusion We found that a small number of studies evaluated adults with 4 years of education or less. Our findings further support the need for the development of specific tools for the assessment of low-educated adults.